Implementation of the Blended Learning Model with Google Classroom in Indonesian Language Learning - Alatas, Mochamad Arifin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the advancements in technology in the field of education. The purpose of this study is to describe the implementation of the blended learning model using Google Classroom in teaching Indonesian language. This research is a qualitative descriptive study. Data collection techniques include interviews, observations, and documentation. The data sources for this research are students, teachers, and documents. Data analysis techniques involve data collection, data reduction, data presentation, and inference. The stages of this research include pre-fieldwork, fieldwork, and reporting. The results of this study provide a description of the Indonesian language learning using the blended learning model with the Google Classroom application, covering the planning, implementation, and evaluation phases. (1) The lesson planning is still based on face-to-face indicators, objectives, and materials. (2) The implementation of the learning process includes teaching materials, methods using communicative audio-lingual and eclectic approaches, as well as utilizing the Google Classroom online learning platform. (3) The evaluation of learning involves process evaluation through daily assessments and outcome evaluation through mid-term and final exams using Google Form and Quizizz. Therefore, the blended learning model with Google Classroom in teaching Indonesian language is effective. However, further development is needed by incorporating various other learning applications.